Poverty Understood as Social Deprivation: A Multi-criteria Model Applied to the City of Uberlândia, Minas Gerais, Brazil - Faria, Rivaldo; Barrozo, Ligia Vizeu (Sociedade & Natureza, 2026)
Urban poverty can be understood as the deprivation of the freedom to access goods and values considered important within a given society. It is a complex phenomenon to evaluate, as it requires multidimensional measures adapted to local realities. This study aims to develop and apply a multi-criteria model to assess urban poverty in Uberlândia, the second-largest city in the state of Minas Gerais, Brazil. The methodology was based on the selection and prioritization of indicators derived from the 2022 Demographic Census of IBGE. Fifteen indicators were selected, covering the dimensions of income, education, demographics, neighborhood surroundings, and housing conditions. These indicators were standardized through linear normalization, weighted using the Analytic Hierarchy Process (AHP), and aggregated via weighted linear combination. The outcome was the construction of the Social Deprivation Index of Uberlândia (IPSUDI), ranging from 0 to 1 and expressed in five classes defined using the natural breaks method. The analyses employed exploratory spatial data techniques and dependency assessment using Global and Local Moran’s I statistics. The results revealed clusters of high social deprivation throughout the peripheral zones of Uberlândia, contrasting with low-deprivation areas in the central, southern, and parts of the eastern regions. High-deprivation areas were found to concentrate younger populations and higher proportions of Black and Brown residents, whereas low-deprivation areas tended to be older and predominantly White. The study concludes that poverty in Uberlândia is a spatially structured and socially determined phenomenon, reproducing racial and generational inequalities. The multi-criteria model proved to be an effective tool for evaluating intraurban poverty, reinforcing the need for integrated public policies that address the multiple dimensions of deprivation and the structural mechanisms that perpetuate inequality.